If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -3b + -2a = 0 Reorder the terms: a + -2a + -3b = 0 Combine like terms: a + -2a = -1a -1a + -3b = 0 Solving -1a + -3b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3b' to each side of the equation. -1a + -3b + 3b = 0 + 3b Combine like terms: -3b + 3b = 0 -1a + 0 = 0 + 3b -1a = 0 + 3b Remove the zero: -1a = 3b Divide each side by '-1'. a = -3b Simplifying a = -3b
| 25x-30=10x | | x^2+y^2-4x+6y+8=0 | | -10-(-2)= | | 143-2x=43x+18 | | 2.3x-5.4=-10 | | 7(x-3)-4x=-16 | | (x+1)=0 | | (2x+9)=x-3 | | 6x+18y=24 | | 18x+6y=24 | | 8(3n-2)= | | 14-10x=48-24x | | 6x+16-x=7x+4 | | 3.2= | | 6(-2x-1)=-11(x+1) | | H+6=-22 | | -96-7x=9x+13 | | 3(y-4)=y-6 | | Ay+6=14 | | 6x+3.50=33.20 | | 9-3r=13 | | 6x+1=-92-7x | | 3(2x+1)-5=4(x-3) | | 2t-2y= | | y=x^3+7x^2-245x+35 | | 18=-1.8 | | -52-3=3x+20 | | 2x+15=63-5x | | 6x+5-3x=18+4x | | 1.2=2.5-3b | | 16x^2+16x-1=0 | | 4x^2+6=13 |